Gender dan Domestifikasi Perempuan (Pendekatan Kodikologi Visual Naskah Dewi Murtasiyah) - Fajar Wijanarko (UIN Raden Mas Said Surakarta, 2018)
Manuscript entitled Dewi Murtasiyah (abbreviated DM) is one of collection from Sonobudoyo Museum. The text was written in Javanese and Arabic which told about Murtasiyah as a woman on patriarch domination in the 18th century. Inside the text, visual of women in that era were presented. Through the method of library research and philology and codicologyâ€™s study, women blaming in the text would be presented. The aim of this research is to describe gender construction in the text, such as (1) women and her domestication, (2) women identic behaviour, and (3) anatomy of woman fashion.Â